Crowdsourcing digital history online - Valatsou, Despoina (Historein, 2014)
Digital history, among other things, offers the possibility for people to collaborate and work together on historical projects online. The notion of crowdsourcing is essential in this process, as well as in the theoretical study and approach of the field of digital humanities.